Pengaruh Inovasi Produk Pistachio Kunafa terhadap Minat Beli Konsumen di Starmoon Cake Shop Surabaya: Penelitian - Cindita Ginting; Yanuar Rafif Rizqullah (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Competition in the culinary industry is becoming increasingly fierce, necessitating product innovation to enhance competitiveness and attract consumer purchase interest. This study aims to analyze the effect of Pistachio Kunafa product innovation on consumer purchase interest at Starmoon Cake Shop Surabaya. The research employs a quantitative method with a survey approach. The sample consists of 145 respondents who are customers of Starmoon Cake Shop, obtained using the total sampling technique. In conclusion, Pistachio Kunafa product innovation significantly contributes to increasing consumer purchase interest at Starmoon Cake Shop Surabaya. Therefore, innovation strategies focusing on novelty, uniqueness, material quality, and added value should be continuously developed to maintain competitiveness and attract consumer attention in the premium culinary industry.